Desenvolvimento de uma plataforma analítica para aquisição de imagens moleculares em tecidos animais - Pratavieira, Marcel [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
New developments in mass spectrometry offer currently new opportunities for studies involving the specific localization of molecular ions directly in tissue samples. An example of recent advances in mass spectrometry was the development of technique Mass Spectral Imaging (MALDI MSI) that allows spatial analysis of chemical distribution patterns in intact tissues. This technique uses the sensitivity and specificity of mass spectrometry for mapping compounds distribution and to produce stereo spatial images, like a ``chemical photography´´, of molecules present in histological sections. Thereby, it´s possible to study molecular interactions, complexity and relative abundance of biomolecules. In this work, it was developed a new analytical platform for MALDI MSI in honeybee Apis mellifera brain, which make possible to study the spatial distribution of some physiologically important neuropeptides (Nps) – allatostatin (AST) and tachykinin (TRP). These Nps were studied in the honeybee brain with 20 days of age, comparing individuals who had aggressive behavior excited (aggressive individuals) and individuals who have not exercised aggressive behavior (control individuals). After mass spectrometer analysis, the mass spectra were converted into images, creating density maps for each mass/charge ratio distribution. In this study, it was identified two Nps protein precursor and some Nps belonging to ASTs and TRPs classes. The results suggest that AST and TRP precursors underwent a rapid cleavage and subsequent transport of mature Nps for different brain regions. A different Nps profile was observed in different brain regions, including qualitative and quantitative relative differences between non-aggressive and aggressive groups. These differences demonstrate the brain complexity of the studied insects and the Nps heterogeneous distribution, indicating that these molecules act in specific brain regions and that they can act in aggressive...

Avanços na espectrometria de massas oferecem atualmente uma ótima oportunidade para estudos na investigação de interações moleculares em amostras de tecido. Um exemplo destes avanços foi o desenvolvimento da técnica MALDI Mass Spectral Imaging (MALDI MSI) voltada para a análise da distribuição espacial de compostos químicos em cortes histológicos. Essa técnica utiliza a sensibilidade e a especificidade da espectrometria de massas para mapear e produzir imagens bidimensionais, uma ‘’fotografia química’’, de moléculas presentes em cortes histológicos, proporcionando o estudo da interação molecular, complexidade e abundância relativa de biomoléculas. Neste trabalho, foi desenvolvida uma nova plataforma analítica para MALDI MSI em cérebro de abelhas Apis mellifera, que possibilitasse o estudo da distribuição espacial de alguns neuropeptídeos (Nps) importantes fisiologicamente (alatostatina – AST e taquicinina – TRP). Esses Nps foram estudados no cérebro de abelhas operárias com 20 dias de idade, comparando indivíduos que tiveram o comportamento agressivo estimulado (indivíduos “agressivos”) e indivíduos que não exerceram o comportamento agressivo (indivíduos controle). Após as análises de espectrometria de massas, os espectros de massas foram convertidos em imagens, gerando mapas de densidade de distribuição para cada relação massa/carga. Nesse estudo foram identificadas duas proteínas precursoras de Nps e alguns Nps pertencentes à classe das ASTs e TRPs. Os resultados sugerem que os precursores AST e TRP sofreram uma rápida clivagem e sucessivo transporte dos Nps maduros, para diferentes regiões do cérebro. Um perfil diferente de Nps foi observado em diferentes regiões do cérebro, incluindo diferenças qualitativas e quantitativas relativas entre os grupos não-agressivo e agressivo. Essas diferenças demonstram a complexidade do cérebro desses insetos, e a distribuição heterogênea dos...
Keywords: Proteínas; Moleculas - Imagem; Neuropeptídeos; Espectrometria de massa; Neurobiologia; Abelha